The Effectiveness of Arabic Language Learning using the PAIKEM Method for Class V Students at MI Al-Ma'had An-Nur Bantul Yogyakarta Academic Year 2023/2024: Efektivitas Pembelajaran Bahasa ARAB Menggunakan Metode PAIKEM untuk Siswa Kelas V di MI MI Al-Ma'had An-Nur Bantul Yogyakarta Tahun Pelajaran 2023/2024 - Budi Pratama; Agung Setiyawan; Boby Bagas Purnama; Khairul Abdillah Harahap (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
The background of this research is to minimize learning methods depending on the student's situation and situation. Therefore, studies aim to decide the impact of the PAIKEM method's effectiveness on Arabic language learning for class V students at MI Al-Ma'had An-nur Bantul Yogyakarta in the 2023/2024 academic year. This form of study is a test that uses a quantitative descriptive technique. The populace of this observation had been college students in training V A, B, and C at MI Al-Ma'had An-nur Bantul Yogyakarta. The study sample consisted of classes V, A, and B, every class numbering 15 students. The sample for this research was selected using a purposive sampling technique statistics series through tests, observations, interviews, and documentation. Hypothesis testing in this research uses the Independent Samples t-test, calculated using the SPSS version 25 application. Based on the research results, results of the Independent Samples T-test show the PAIKEM learning method has a success rate difference of 84.05 with the effective category, and Traditional learning methods have a difference in the success rate of 64.05 with the ineffective category existing. PAIKEM This approach is very suitable for use because it's miles more effective in improving student mastering results in Arabic language knowledge. It is an appropriate date for the situations and conditions of students within the magnificence. Keywords: Arabic Learning, Effectiveness, PAIKEM Method